Effects of Nickel on Human and Fish Red Blood Cells. Issue 4 (6th August 2007) - De Luca, Grazia; Gugliotta, Tiziana; Parisi, Giulia; Romano, Pietro; Geraci, Antonella; Romano, Orazio; Scuteri, Adriana; Romano, Leonardo
Abstract : The objective of this study was to assess the effects of nickel chloride on human and rainbow trout erythrocytes in vitro. The cells were incubated with 0, 0.5 and 1 mM nickel chloride for 1 h at pH 7.40 and 25°C, then K + efflux, SO4 2− uptake and GSH and GSSG concentrations were measured. In both kind of cells, "high concentration" nickel treatment increased KCl efflux with respect to the control. The SO4 2− uptake was not significantly different at "low nickel concentration" but was lower in erythrocytes treated with 1 mM nickel chloride; the rate constant of SO4 2− uptake decreased by 35% in human erythrocytes and by 44% in fish erythrocytes. Nickel chloride also acts on cellular metabolism and in particular on erythrocyte glutathione peroxidase with consequent increase in oxidative stress; the data show a significant decrease in intracellular GSH in both human (25%) and fish erythrocytes (18%) after treatment with nickel chloride, with concomitantly high GSSG concentrations and lower GSH/GSSG ratios.